PERBANDINGAN KEKERASAN DAN KETAHANAN ABRASI PROSES PELAPISAN KROMISASI, BORONISASI DAN VANADISASI PADA BESI COR KELABU[Comparison of Hardness And Abrassion Resistant of Boronizing Vanadizing and Chromizing Coated Gray Cast Iron] - Romijarso, Toni Bambang (Jurnal Metalurgi, 2013)
In order to increase the hardness and abrassion resistance of gray cast iron, chromizing, vanadizing and boronizing treatments were carried out at 875°C and holding time variously for 1; 3 and 5 h. Chromizing, vanadizing and boronizing treatments obtained white layer on the surface of gray cast iron. This layer increase due to increasing holding time. A thickness for chromizing layer that contain of chromium carbide (CrxCy) is 85 μm with hardness value 1250 VHN and abrassion resistant 0.0029 g/m. The layer thickness of vanadizing and boronizing that contain of ferrovanadida (Fe2V) and ferroboronida (Fe2B) were 19.26 μm and 50 μm for 5 h holding time, respectively. Hardness values of vanadizing and boronizing were 742 and 810.5 VHN, while abrassion resistant for both of these processes were 0.0061 g/m and 0.0102 g/m. Chromized has higher diffusion rate compared to vanadizing and boronizing. Diffusion rates reached approximately 1,254x10-9; 1,034x10-10 and 1,157x10-9 cm2s-1, respectively. The results showed that chromizing obtained hardness and abrassion resistance more higher than others.